2017
DOI: 10.1590/1809-4430-eng.agric.v37n2p302-314/2017
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Diesel Engine Fuelled With Four Vegetable Oils, Preheated and at Engine Working Temperature

Abstract: ABSTRACT:With the rise of restrictions imposed by law for gases emission, several technologies both for petrodiesel (PD) or diesel engines are been applied, such as the sulfur reduction and the injection electronic command, followed of gases recirculation and/or after-treatment. The utilization of biofuels is considered as an interesting option for pollutants reduction. In this study was evaluated the performance on short duration tests (minor period than the factory indication of the lubricant lifespan) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Similar trend and range of exhaust gas temperatures were reported by Delalibera et al 6 The amount of fuel injected increases with the engine load in order to provide the power output and hence the heat release with increase in load applied. 6,36,38 At all loads, diesel and SVOs are found to have alternate lowest temperature. The SVO fuels contain oxygen which enables the combustion process and hence the exhaust gas temperatures are higher.…”
Section: Emission Characteristicssupporting
confidence: 83%
See 2 more Smart Citations
“…Similar trend and range of exhaust gas temperatures were reported by Delalibera et al 6 The amount of fuel injected increases with the engine load in order to provide the power output and hence the heat release with increase in load applied. 6,36,38 At all loads, diesel and SVOs are found to have alternate lowest temperature. The SVO fuels contain oxygen which enables the combustion process and hence the exhaust gas temperatures are higher.…”
Section: Emission Characteristicssupporting
confidence: 83%
“…[1][2][3] The use of plant oils in diesel engines will support the utilization of indigenous renewable energy resources in not only achieving sustainable economic development but also promoting ''clean and green energy'' for preserving the natural environment. [4][5][6][7] Vanuatu suffers from the disadvantages of small population, distance from the world market, scattered nature of archipelagos and frequent natural disasters. At the same time, coconut (cocos nucifera), tamanu (calaphyllum inophyllum), and nangae (canarium indicum) are good natural resources in Vanuatu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fuel modification in the way of blending, emulsification or oxygenation is the simplest solution for emission reduction, neither engine modification for alternative fuel use. Furthermore, preheating of oil is not the best solution due to increase of fuel consumption for preheated oils than those without preheating, while no effect of this heating process was noticed on diesel engine opacity [5].…”
Section: Introductionmentioning
confidence: 98%
“…In Diesel cycle engines, recent studies have equally demonstrated the importance of the parameters of consumption, performance and emissions for diesel/alcohol blends (ethanol, methanol and butanol) and little is known (Kumar et al, 2013;Putrasaria et al, 2013;Gonca, 2014;Abedim et al, 2016;Fayyazbakhsh & Pirouzfar;Kumar & Saravanan, 2016); and also fuel preheating when considering vegetable oils (Delalibera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%